The Triad Design of Order 19 - Abu-Saa, T. M.; Ibrahim, Haslinda (Natural Sciences Publishing Cor., 2012)
In this paper we present a new method to construct the triad design of order 19,TD(19). First we construct the compatible factorization of order 19, CF(19).Then we build the starter of triad design of order 19, STD(19) using interval techniques of the number of triples in the design. Finally by using addition modular 19 to STD(19) we develop TD(19)